2013
DOI: 10.1021/om400047j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of Silyl Iron, Cobalt, and Nickel Complexes Bearing a [PSiP]-Pincer Ligand via Si–H Bond Activation

Abstract: The synthesis and characterization of a series of Ni, Co, and Fe complexes bearing a tridentate bis(phosphino)silyl ligand (κ 3 -(2-Ph 2 PC 6 H 4 ) 2 SiMeH, [PSiP]-H, 1) are reported. 1 reacted with Ni(PMe 3 ) 4 to afford the mononuclear nickel(0) complex [η 2 (Si−H)-PSiP]Ni(PMe 3 ) (2). The halogeno nickel complexes [PSiP]Ni(X)(PMe 3 ) (X = Cl (3), Br (4), I (5)) were synthesized in the reactions of 2 with Me 3 SiCl or MeHSiCl 2 , EtBr, and MeI. Complex 2 underwent ligand substitution of PMe 3 by CO to give [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 52 publications
8
88
1
2
Order By: Relevance
“…While the one electron reduction of Co II halide complexes proved facile, access to Co III species supported by Cy‐PSiP ligation was significantly more challenging. This is in contrast to observations by Sun and co‐workers, who have reported on readily isolable Co III complexes supported by closely related diphenylphosphino PSiP derivatives. Attempted oxidative addition reactions involving (Cy‐PSiP)Co(PMe 3 )N 2 were generally unsuccessful, with the sole exception of H 2 , which reacted to afford the dihydride complex (Cy‐PSiP)Co(PMe 3 )(H) 2 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…While the one electron reduction of Co II halide complexes proved facile, access to Co III species supported by Cy‐PSiP ligation was significantly more challenging. This is in contrast to observations by Sun and co‐workers, who have reported on readily isolable Co III complexes supported by closely related diphenylphosphino PSiP derivatives. Attempted oxidative addition reactions involving (Cy‐PSiP)Co(PMe 3 )N 2 were generally unsuccessful, with the sole exception of H 2 , which reacted to afford the dihydride complex (Cy‐PSiP)Co(PMe 3 )(H) 2 .…”
Section: Discussioncontrasting
confidence: 99%
“…The X‐ray crystal structure of 1‐PMe 3 revealed that this complex adopts distorted trigonal bipyramidal geometry in the solid state, with the chloride ligand and the silyl donor bound in the apical positions, and the phosphines occupying the equatorial positions. This is in contrast to the structure of (Ph‐PSiP)CoCl(PMe 3 )[10a] and the related bis(diphenylphosphanyl)silyl complex [κ 3 ‐C 6 H 4 (Ph 2 PCH 2 N) 2 SiMe]CoI(PMe 3 ),[10b] in which the PMe 3 ligand is coordinated in the apical position trans to Si. Solution magnetic moment measurements for 1‐PMe 3 and 2‐PMe 3 (room temperature, [D 6 ]benzene) resulted in µ eff values of 1.89 and 1.65 µ B , respectively, consistent with an S = 1/2 magnetic ground state in each case.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…This indicates that two PMe 3 ligands are chemically different. The spectroscopic characteristics are comparable with those of complex 1 . In the 31 P NMR spectrum of 4 a “dt” peak at 1.7 and a multiplet peak at 6.3 ppm for the two PMe 3 ligands and a doublet at 88.7 ppm for –P i Pr 2 groups were recorded in the integral ratio of 1 (PMe 3 ): 1 (PMe 3 ): 2 (‐P i Pr 2 ).…”
Section: Resultssupporting
confidence: 62%
“…Complexes 1–3 were prepared according to the literature procedures . Complex 4 was obtained from the combination of bis( o ‐(diisopropylphosphino)phenyl)methylsilane with Fe (PMe 3 ) 4 in THF at 0 °C under Ar atmosphere (Scheme ).…”
Section: Resultsmentioning
confidence: 99%